Cruciform scripture: cross, participation, and mission - Skinner, Christopher W.; Gupta, Nijay K.; Johnson, Clinton Andrew; Strait, Drew J. (William B. Eerdmans Publishing Company, 2021)
"A collection of essays that build upon and honor the work of Michael Gorman"--